Causal association pathways between fetuin-A and kidney function: a mediation analysis - Philip Etabee Bassey; Pawin Numthavaj; Sasivimol Rattanasiri; Piyamitr Sritara; Mark McEvoy; Boonsong Ongphiphadhanakul; Ammarin Thakkinstian (Journal of International Medical Research, 2022)
Objective Body mass index (BMI), uric acid, diabetes mellitus, and hypertension are risk factors for reduced kidney function and are associated with fetuin-A levels, but their causal pathways remain unclear. The objective of this study was to investigate this knowledge gap. Methods A repeated cross-sectional design was used to assess causal pathway effects of fetuin-A on the estimated glomerular filtration rate (eGFR), which is mediated through BMI, uric acid, diabetes mellitus, and hypertension. Results Among 2305 participants, the mean eGFR at baseline decreased from 98.7 ± 23.6 mL/minute/1.73 m 2 in 2009 to 92.4 ± 22.9 mL/minute/1.73 m 2 in 2014. Fetuin-A was significantly associated with eGFR , suggesting that increasing fetuin-A levels predict a decrease in eGFR. Additionally, the indirect effect of fetuin-A on eGFR, as assessed through BMI, was also significant. The effects of fetuin-A on eGFR through other mediation pathways showed variable results. Conclusions Our study revealed a possible role of fetuin-A in the etiology of declining renal function through mediating body mass index, uric acid, diabetes mellitus, and hypertension via complex causal pathways. Further studies to clarify these mediated effects are recommended.